RESULTS FROM TIEN-SHAN SURVEY TO SEARCH FOR VARIABLE STARS: OBSERVATIONS, TARGET SELECTION AND DATA PROCESS - Serebryanskiy, A.; Kusakin, A.; Reva, I.; Omarov, Ch. (Academic Scientific Journal of Computer Science, 2020)
We present the first results of the photometric survey at Tien-Shan Observatory (TSO) of the fields around Galactic equator using Zeiss-1000 telescope. Here we report on criteria selection of target fields, observation strategy and statistics of photometric observations. We also provide description of data process and differential photometric reduction to extract differential light curves. In total, 23 fields in the range of 40°-210° Galactic longitude and ±5° Galactic latitudes were observed during 2014-2018. Each filed was observed for at least 3 hours long with cadence range 30-180 sec in Johnson-Cousine filters V and R, or in integrated light. As a result, long duration light curves for about 10 000 stars were obtained. A visual inspection of the light curve from each run was carried out for each star in the field that successfully passed the photometry process in at least 70%-75% of the total duration of observations, which made it possible to identify stars with unambiguous signs of variability. Analysis of the light curves of these stars leads to the identification of 33 variable stars. Among them, 31 stars are previously unknown variables not presented in catalogs of variable stars.